Electronic publishing and the future of the book - T.D. Wilson (Information Research: An International Electronic Journal)
A paper delivered at the International Conference on Book Science to commemorate the 450th anniversary of the first Lithuanian book, Vilnius University, Lithuania, 24-28 September, 1997.